Diagnosis and treatment of osteochondral lesions of the ankle: current concepts - Marcelo Pires Prado; John G. Kennedy; Fernando Raduan; Caio Nery (Revista Brasileira de Ortopedia)
ABSTRACT We conducted a wide-ranging review of the literature regarding osteochondral lesions of the ankle, with the aim of presenting the current concepts, treatment options, trends and future perspectives relating to this topic.